2016
DOI: 10.18632/oncotarget.11378
|View full text |Cite
|
Sign up to set email alerts
|

Not all 1p/19q non-codeleted oligodendroglial tumors are astrocytic

Abstract: Although 1p/19q codeletion is the genetic hallmark defining oligodendrogliomas, approximately 30-40% of oligodendroglial tumors have intact 1p/19q in the literature and they demonstrate a worse prognosis. This group of 1p/19q intact oligodendroglial tumors is frequently suggested to be astrocytic in nature with TP53 and ATRX mutations but actually remains under-investigated. In the present study, we provided evidence that not all 1p/19q intact oligodendroglial tumors are astrocytic through histologic and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…As mentioned in Fuller, G N's study [46], 6 thorny cases of 1p/19q FISH-positive and IDH wild-type did not meet the diagnostic criteria for "oligodendroglioma, IDH mutations, and 1p/19q codeletion." Ho-Keung Ng et, al [50] also found 5 in 185 cases(2.7 %) presented as "IDH wildtype and 1p/19q codeletion" and did not warrant a diagnosis of "oligodendroglioma, IDH mutant and 1p/19q co-deleted." Our results also confirmed the presence of 1p/19q co-deleted and IDH wildtype oligodendrogliomas as described in the above studies.…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned in Fuller, G N's study [46], 6 thorny cases of 1p/19q FISH-positive and IDH wild-type did not meet the diagnostic criteria for "oligodendroglioma, IDH mutations, and 1p/19q codeletion." Ho-Keung Ng et, al [50] also found 5 in 185 cases(2.7 %) presented as "IDH wildtype and 1p/19q codeletion" and did not warrant a diagnosis of "oligodendroglioma, IDH mutant and 1p/19q co-deleted." Our results also confirmed the presence of 1p/19q co-deleted and IDH wildtype oligodendrogliomas as described in the above studies.…”
Section: Discussionmentioning
confidence: 98%
“…Among them, anatomic location plays a crucial role not only for prognosis prediction but also for treatment strategy. It was widely acknowledged that prognosis is poor in midline glioma than non-midline tumor [ 10 ]. Regarding to hemispheric glioma, patient with tumor located in frontal lobe tends to be younger, IDH1 mutation and longer survival time [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The status of 1p19q was determined by FISH (fluorescence in situ hybridization). A case of 50% tumor cells present with reference probe signal ratio to target probe signal more than 2:1 was considered 1p19q codeletion, otherwise we called 1p19q intact [ 10 ]. Molecular information will be integrated into regular pathological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the survival rate was higher in cases with IDH mutation, but no statistical difference was there (p=0.147). The presence of 1p/19q loss has been associated with long overall survival in patients regardless of treatment (21). In our study, the survival rate was 64.3% in cases without 1p/19q loss and 81.6% in cases with 1p/19q loss (p=0.178).…”
Section: Discussionmentioning
confidence: 45%
“…In a study conducted in 987 cases, median survival time was 11.6 years in oligodendrogliomas and 5.6 years in low-grade As. These values are similar for grade III tumors; a study conducted by the European Cancer Treatment and Research Organization-Brain Tumor Group, which included 368 patients, demonstrated that median survival time was 34.7 months in anaplastic oligodendrogliomas (21). IDH mutant tumors have better prognosis regardless of grade (12,22).…”
Section: Discussionmentioning
confidence: 71%